2000
DOI: 10.1046/j.1525-1497.2000.07006.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of depressive symptoms on health-related quality of life in asthma patients

Abstract: OBJECTIVE:To assess the effects of depressive symptoms on asthma patients' reports of functional status and healthrelated quality of life. DESIGN:Cross-sectional study.SETTING: Primary care internal medicine practice at a tertiary care center in New York City. PATIENTS:We studied 230 outpatients between the ages of 18 and 62 years with moderate asthma. Stepwise multivariate analyses were conducted with the AQLQ and SF-36 scores as the dependent variables and depressive symptoms, comorbidity, asthma, and demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
2
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(127 citation statements)
references
References 58 publications
7
110
2
8
Order By: Relevance
“…Adams et al [14] documented that psychological distress and decreased feelings are common in asthmatics. In another study by Manucoso, nearly 50% of asthma patients were found to suffer from clinically signifi cant depressive symptoms, [15] and it was attributed to the stress of having a chronic illness. [16] In clinical samples of children and adolescents, asthma has been associated with presence of an anxiety disorder [17] and depressive symptoms among youth with moderate-to-severe persistent asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Adams et al [14] documented that psychological distress and decreased feelings are common in asthmatics. In another study by Manucoso, nearly 50% of asthma patients were found to suffer from clinically signifi cant depressive symptoms, [15] and it was attributed to the stress of having a chronic illness. [16] In clinical samples of children and adolescents, asthma has been associated with presence of an anxiety disorder [17] and depressive symptoms among youth with moderate-to-severe persistent asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, Höfer et al (Höfer et al, 2006) also observed a significant positive change over time for the physical component summary dimension (PCS) of the SF-36, but not for the mental component summary dimension (MCS). However, other authors (Elliott et al, 2003;Mancuso et al, 2000;Wells et al, 1989) have shown that the SF-36 MCS is a good indicator of depression in general and diseased populations and Tavella et al (Tavella et al, 2010) have even established a threshold score on the SF-36 MCS that would categorise a population with cardiac disease into depressed and non-depressed patients.…”
Section: Factors Related To Health Related Quality Of Life In Coronarmentioning
confidence: 99%
“…[23][24][25] Depressive symptoms were obtained using the 15-item short-form Geriatric Depression Scale, which has been validated in nongeriatric populations generally, as well as specifi cally in younger adults with obstructive lung disease. [26][27][28] Anxiety was assessed using the seven-item anxiety subscale of the Hospital Anxiety and Depression Scale. 29,30 COPD severity was assessed with the Body-Mass, Obstruction, Dyspnea, Exercise (BODE) Index, a multidimensional score which includes FEV 1 , 6-min walk test, BMI, and dyspnea.…”
Section: Measurementsmentioning
confidence: 99%